1990
DOI: 10.1002/pd.1970100206
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of cytogenetic diagnosis after CVS: 1500 cases

Abstract: The cytogenetic results of 1500 chorionic villus samples (CVS) are presented. In these 1500 samples, 23 samples (1.5 per cent) could not be provided with a diagnosis because of laboratory failure. This failure rate dropped from 3 per cent in the first 500 samples to 0.2 per cent in the last 500. In the remaining 1477 samples, 58 (3.9 per cent) chromosomal aberrations were found. Of these, 21 (36 per cent) proved not to represent the karyotype of the fetus proper. Predictive values of (different groups of) chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 15 publications
4
26
0
Order By: Relevance
“…The negative predictive value is 100% since we had no cases with false negative results. The positive predictive value of 66% in this study is comparable to the results of Breed et al (1990), the US collaborative study (Ledbetter et al, 1992) and Los et al (1998), which were 64, 68.4 and 67.8%, respectively. The positive predictive value of 75% in the EUCROMIC study (Hahnemann and Vejerslev, 1997a) is somewhat higher.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The negative predictive value is 100% since we had no cases with false negative results. The positive predictive value of 66% in this study is comparable to the results of Breed et al (1990), the US collaborative study (Ledbetter et al, 1992) and Los et al (1998), which were 64, 68.4 and 67.8%, respectively. The positive predictive value of 75% in the EUCROMIC study (Hahnemann and Vejerslev, 1997a) is somewhat higher.…”
Section: Discussionsupporting
confidence: 76%
“…CVS was performed transcervically between 10 and 12 weeks of gestation as described previously (Breed et al, 1990). Exceptionally, CVS was performed transabdominally in cases of more than 12 weeks' gestation.…”
Section: Methodsmentioning
confidence: 99%
“…Several examples of trisomy 11 CPM have been reported in smaller series: 1/15 autosomal CPM [1], 1/58 [2], 1/17 [7], 1/19 [3].…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancies between the karyotype in chorionic villus sampling (CVS) and the fetal karyotype have been reported in large series [1][2][3][4]. Confined placental mosaicisms (CPM) [5] have been revealed by prenatal diagnosis studies in about 1% of the CVS [4].…”
Section: Introductionmentioning
confidence: 99%
“…Lahdetie and Lakkala [I9921 described mosaicism for trisomy 15 ascertained a t midtrimester amniocentesis. Although a repeat amniocen- Hutton, E, unpublished Ledbetter et al, 1992Purvis-Smith et al, 1992Cassidy et al, 1992Lahdetie and Lakkala, 1992Kalousek et al, 1991Kuller and Laifer, 1991Ohno et al, 1991Eiben et al, 1990Breed et al, 1990Stallard and Sommer, 1989Schulze e t al., 1987Hogge et al, 1986Simoni et al, 1986Lin et al, 1985Mikkelsen, M., 1985Karkut et al, 1985Gimelli et al, 1983Coldwell et al, 1981Kajii et al, 1980 + tesis confirmed trisomy 15 mosaicism and ultrasound examination revealed IUGR, the parents opted to continue the pregnancy. The cord blood sample at birth had a normal karyotype, while umbilical cord, placenta, and fetal membranes had various degrees of trisomy 15 mosaicism.…”
Section: Survival and Clinical Features Of Trisomy 15 Conceptionsmentioning
confidence: 96%